Bioactive Lipids and Lipidomics 2018 - Ollero, Mario; Touboul, David (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
After the coming of age of lipidomics, the science of global lipid analysis has broadened its contribution to the understanding of biological processes. This volume represents a transversal view on the state of the art of research on lipid biology and bioactive lipid molecules. It includes research and review articles on the role of bioactive lipids in diverse domains like cell signaling, neuromuscular transmission, cancer pathophysiology, cardiovascular and rare diseases, antibacterial activity, the emergency of biomaterials, and associated technological and analytical developments. It provides an instantaneous picture of the place of lipidomics and its fields of application, as well as hints about the directions that lipid research may follow in the near future.